Various Character Education Research on Baduy Indigenous People - Sutiapermana, Aden; Malihah, Elly; Somad, Momod Abdul; Komariah, Siti (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2022)
This study aims to 1) analyze these studies from the point of view of the scientific paradigm, 2) determine the paradigm of science that has been done by previous research, and 3) Find untouched research gaps based on the paradigm of science. These three findings are useful as theoretical foundations for conducting subsequent research. Based on this objective, this research uses the method of literature study by utilizing an understanding of the philosophy of science to see the nature of the paradigm of science that underlies each research. The research process was carried out in three steps: the first began with conducting a literature review of several articles of character education research reports on the Baduy indigenous people; second, interpret by categorizing each research report based on the basic paradigm of the social sciences; and third, find a scientific paradigm that has not been done in previous studies. As a result, character education research that has been carried out has used various paradigms of social science, ranging from philosophy and psychology to sociology. However, if examined more deeply based on the perspective of the sociological paradigm, character education studies in the Baduy indigenous community are still within the scope of micro-sociology in the form of the role of the family in shaping character, no one has used the macro-sociological paradigm that considers the roles of social structures and systems in shaping community adherence to pikukuh (customary rules).